2018
DOI: 10.1002/lary.27350
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Dysphonia Classification of DSI and AVQI

Abstract: 2c. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…8 In laryngology, acoustic measurements are especially used as indicators of the efficiency of speech therapy, medical or surgical treatments in many conditions (ie, nodules, 9 polyps, 10 laryngopharyngeal reflux, 11 and or aging voice). 12 Furthermore, some acoustic measures are included in the calculation of many multidimensional scores, such as the dysphonia severity index 13 or the acoustic voice quality index, 14 that are useful in some public health systems to obtain reimbursement of speech therapy. 15 In two recent systematic reviews focusing on the evolution of acoustic measurements throughout treatment of laryngopharyngeal reflux (LPR) and idiopathic Parkinson's disease (IPD), it was reported that the method used for the measurement of acoustic parameters (ie, vowel types; number of samples; and selection of the time interval over which the acoustic parameters are measured) significantly varies between studies, which is associated with controversial results and unclear conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…8 In laryngology, acoustic measurements are especially used as indicators of the efficiency of speech therapy, medical or surgical treatments in many conditions (ie, nodules, 9 polyps, 10 laryngopharyngeal reflux, 11 and or aging voice). 12 Furthermore, some acoustic measures are included in the calculation of many multidimensional scores, such as the dysphonia severity index 13 or the acoustic voice quality index, 14 that are useful in some public health systems to obtain reimbursement of speech therapy. 15 In two recent systematic reviews focusing on the evolution of acoustic measurements throughout treatment of laryngopharyngeal reflux (LPR) and idiopathic Parkinson's disease (IPD), it was reported that the method used for the measurement of acoustic parameters (ie, vowel types; number of samples; and selection of the time interval over which the acoustic parameters are measured) significantly varies between studies, which is associated with controversial results and unclear conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, continuous speech is more representative of daily speech and, therefore, can be considered to be more 'ecologically valid' [6]. Several studies in the last decade already demonstrated the robust diagnostic accuracy of AVQI [5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], its consistent and high concurrent validity [5,[7][8][9][10][11][12][13][14][15][16][17]19,[21][22][23][24][25] and its high sensitivity to voice changes across voice therapy [8,12,16,18,21]. Furthermore, studies validating the use of AVQI in different languages showed diagnostic accuracy according to inter-language phonetic differences [9][10][11][12]…”
Section: Introductionmentioning
confidence: 99%
“…Findings from prior research indicated no significant correlations between the subjects’ age, sex, AVQI, and ABI measurements [ 31 , 36 ]. However, DSI values were found to be unrelated to sex but showed a slight correlation with age [ 43 ]. Consequently, in the current study, the control and patient groups were deemed appropriate for analyzing the investigated MAVI data, even though these groups were not matched in terms of sex and age.…”
Section: Resultsmentioning
confidence: 99%
“…Based on auditory-perceptual judgment, the research team concluded that the AVQI appears to be useful in defining variations in vocal quality state and distinguishing between normal and dysphonic voices [ 21 ]. However, the consequent study yielded that both these MAVIs can also differentiate between vocally healthy and voice-disordered subjects in comparison with the dysphonia classification based on the diagnosis of laryngeal disorder, thus enabling the quantification of abnormality [ 43 ]. In 2023, Penido et al evaluated the AVQI, ABI, and DSI for speech–language pathologist decision-making in the assessment of teachers’ voice complications.…”
Section: Introductionmentioning
confidence: 99%